2014
DOI: 10.1002/anie.201408493
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogenated Anatase: Strong Photocatalytic Dihydrogen Evolution without the Use of a Co‐Catalyst

Abstract: Abstract:In the present work we show, how a high pressure hydrogenation of commercial anatase or anatase/rutile powder can create a photocatalyst for hydrogen evolution that is highly effective and stable without the need of any additional co-catalyst. This activation effect can not be observed for rutile. For anatase/rutile mixtures, however, a strong synergistic effect is found (similar to findings commonly observed for noble metal decorated TiO 2 ). ESR measurements indicate the intrinsic co-catalytic activ… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
86
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
2

Relationship

4
6

Authors

Journals

citations
Cited by 93 publications
(91 citation statements)
references
References 40 publications
(82 reference statements)
4
86
0
Order By: Relevance
“…Black TiO 2 can be prepared using different polymorphs [83][84][85][86] and following various reductive treatments, although the easiest is certainly H 2 reduction at temperature between 400 and 700°C [83,86,87]. HR-TEM analysis demonstrated that black TiO 2 nanoparticles present a nearly stoichiometric, disordered surface while oxygen vacancies are located in the bulk [83,87].…”
Section: Increasing Activity Under Visible Light: Self-doping Vs Surfmentioning
confidence: 99%
“…Black TiO 2 can be prepared using different polymorphs [83][84][85][86] and following various reductive treatments, although the easiest is certainly H 2 reduction at temperature between 400 and 700°C [83,86,87]. HR-TEM analysis demonstrated that black TiO 2 nanoparticles present a nearly stoichiometric, disordered surface while oxygen vacancies are located in the bulk [83,87].…”
Section: Increasing Activity Under Visible Light: Self-doping Vs Surfmentioning
confidence: 99%
“…Titanium dioxide is known as an inexpensive, nontoxic, and photostable n‐type semiconductor, and virtually it has been extensively used in the photocatalytic H 2 ‐evolution reaction from water splitting . However, TiO 2 alone is not effective for photoproduction of H 2 for its rapid recombination rate of photoexcited carriers and high overpotential for H 2 evolution . Although the most common noble metal cocatalysts (e.g., Pt, Pd, or Au) can act as electron transfer mediator and further prolong the lifetime of charge carriers to achieve high activity in H 2 evolution, they are too scarce and expensive .…”
Section: Introductionmentioning
confidence: 99%
“…The authors ascribed the finding to an arrowing of the band gap from 3.2 to 1.8 eV,o wing to the formation of an amorphous H-containing shell around the crystallinec ore of the anatase nanoparticle, which led to broad visible light absorption by the 'black' TiO 2 . [14][15][16][17][18] Another remarkabler ecently reported property is that TiO 2 nanoparticles, after ah igh pressure/high temperature treatment in H 2 and in the absence of any noblem etal cocatalyst, are able to photocatalytically generate H 2 .T his intriguingf eature has been reportedf or nanotubes, [19] powders, and nanoparticles of TiO 2 , [20] as well as for Ti/TiO 2 core-shell structures. [14][15][16][17][18] Another remarkabler ecently reported property is that TiO 2 nanoparticles, after ah igh pressure/high temperature treatment in H 2 and in the absence of any noblem etal cocatalyst, are able to photocatalytically generate H 2 .T his intriguingf eature has been reportedf or nanotubes, [19] powders, and nanoparticles of TiO 2 , [20] as well as for Ti/TiO 2 core-shell structures.…”
mentioning
confidence: 96%